Epidermal innervation in type 1 diabetic patients: a 2.5-year prospective study after simultaneous pancreas/kidney transplantation - Boucek, Petr; Havrdova, Terezia; Voska, Ludek; Lodererova, Alena; He, Lan; Saudek, Frantisek; Lipar, Kvetoslav; Adamec, Milos; Sommer, Claudia (Diabetes care, 2008)
OBJECTIVE: To assess the effect of normoglycemia following simultaneous pancreas/kidney transplantation (SPK) on neurological function and intraepidermal nerve fiber density (IENFD) in patients with type 1 diabetes. RESEARCH DESIGN AND METHODS: We performed vibration perception threshold (VPT) testing and autonomic function testing (AFT) and assessed IENFD in skin biopsies from the lower thigh and upper calf in 14 healthy control subjects and 18 patients with type 1 diabetes at the time of and at 21-40 (median 29) months post SPK. RESULTS: At baseline, significantly increased VPTs, pathological AFT results, and severe reduction in IENFD were present in SPK recipients. After SPK, an increase of IENFD in the thigh of more than one epidermal nerve fiber per millimeter was noted in three patients (median 4.1, range 1.9-10.2), but changes were not significant for the group as a whole. CONCLUSIONS: We conclude that either irreversible nerve damage might be present in some SPK recipients or that longer periods of normoglycemia might be needed to allow nerve regeneration.
Keywords: diabetické nefropatie; diabetes mellitus 1. typu; vibrace; percepce; Diabetic Neuropathies; transplantace slinivky břišní; následné studie; Perception; Biopsy, Needle; krevní glukóza; Adult; Pancreas Transplantation; Prospective Studies; dospělí; kůže; referenční hodnoty; nervová vlákna; Nerve Fibers; Follow-Up Studies; jehlová biopsie; Vibration; Reference Values; Diabetic Nephropathies; lidé; Skin; Kidney Transplantation; transplantace ledvin; Humans; Diabetes Mellitus, Type 1; diabetické neuropatie; Blood Glucose; prospektivní studie